اللغة العربية في عصر العولمة: تحديات الأدب واللغة (Al-Qamar, 2024)
This study addresses the challenges facing the Arabic language in the era of globalization. Arabic is one of the oldest Semitic languages and has significantly influenced the development of civilizations and cultures. As the language of the Quran, Arabic has received considerable attention throughout history, making it a symbol of identity and belonging. However, today, the Arabic language faces serious challenges, primarily competition from the English language and the dominance of colloquial dialects. This research aims to explore the importance of the Arabic language and its unique characteristics, as well as to investigate ways to confront these challenges. The study employs a descriptive methodology to analyze the phenomenon by observing current changes in the language and anticipating its future. It also aims to raise awareness about the importance of preserving and developing the Arabic language to meet the demands of the modern era.
Keywords: Arabic Language; Linguistics; Globalization; Dialects; Literary Challenges